Three dimensional hierarchical network structure of S-NiFe2O4 modified few-layer titanium carbides (MXene) flakes on nickel foam as a high efficient electrocatalyst for oxygen evolution. (10th February 2019) - Tang, Yi; Yang, Chenhui; Yang, Yawei; Yin, Xingtian; Que, Wenxiu; Zhu, Jianfeng
Abstract: Oxygen evolution reaction (OER) is an important kinetic process in many important renewable energy applications, while high-efficiency electrocatalysts, especially efficient non-precious metal catalysts, are very essential to overcome substantial overpotential and sluggish kinetics of OER. Here, three-dimensional (3D) Ti3 C2 based conductive network structure was firstly constructed by an absorption of 2D few-layer Ti3 C2 flakes (MXene) onto 3D nickel foam (NF) network, and then ultra-small sulfur-incorporated nickel ferrite nanosheets (S-NiFe2 O4 ) were grown on the 3D Ti3 C2 based conductive network structure (abbreviated as S-NiFe2 O4 @Ti3 C2 @NF) by combining a facile thiourea-assisted electrodeposition process with a low-temperature calcination process. Results indicate that the as-fabricated S-NiFe2 O4 @Ti3 C2 @NF hybrid electrode exhibits a superior OER activity, which includes only 1.50 V vs. RHE to afford a current density of 20 mA cm −2, a Tafel slope of 46.8 mV dec −1 and excellent catalytic stability in 1 M KOH. Excellent OER performances are attributed to the favorable 3D hierarchical network structure and relatively fast electron transport provided by the few-layer Ti3 C2 flakes matrix, good catalytic activity and abundant catalytic active sites from the ultra-small S-NiFe2 O4 nanosheets, synergistically. This work could open a feasible way for achieving a new type of 3D MXenes based hierarchical network structure for renewable energy applications. Graphical abstract: Image 1